Gender disparities in food shopping patterns: Evidence from rural Bangladesh, India, and Nepal - Boncyk, Morgan; Gupta, Ishika; Isanovic, Sejla; Avula, Rasmi; Choudhury, Samira; Scott, Samuel P.; Blake, Christine E.; Frongillo, Edward A.; Krupnik, Timothy J.; Menon, Purnima; Veettil, Prakashan Chellattan (Elsevier, 2024)
Objectives: Understanding gender differences in food acquisition and decision-making is needed to inform policies promoting healthy diets for all. We compare food acquisition patterns and preferences of men and women in three South Asian countries. Methods: In 2023, 4,000 rural households with adolescents were randomly selected with a proportional probability per village in five districts: Rajshahi and Rangpur in Bangladesh, Nalanda in India, and Banke and Surkhet in Nepal. Adults primarily responsible for household food purchases were asked where, why, and how they acquired frequently consumed foods. Foods were categorized as healthy or unhealthy. Analyses compared shoppers’ responses by country, district, and gender. Results: Food shoppers (n=2,555) were primarily men in India and Bangladesh, women in Nepal, and averaged 41 years of age. Food purchases were mostly from retail outlets in India and Nepal, and wholesale open-air markets in Bangladesh. Shoppers’ preferred purchasing source was primarily based on cost and distance. On average, shoppers traveled 2.9 km to purchase food, women 0.9 km further than men. Unhealthy foods were purchased more than healthy foods (2.6 vs 1.3 times/mo), with biscuits most often (3.8 times/mo). Nepal had 66% lower food purchase frequency than Bangladesh. Purchases varied by gender and country: healthy and unhealthy foods were purchased more by men in Bangladesh and women in India. In Nepal, men purchased more healthy foods than women, and women purchased more unhealthy foods than men. In India and Nepal, shoppers found unhealthy foods as more accessible and affordable than healthy foods; in Bangladesh, shoppers found healthy foods more accessible and affordable. Perceptions varied by gender and country: men found healthy and unhealthy foods more accessible and affordable than women in Bangladesh and Nepal, in India, such perceptions were predominant among women. With more income, men and women would purchase more animal-sourced foods and produce and fewer unhealthy foods. Women would purchase more legumes and grains than men. Conclusions: In rural South Asia, women perceived healthy foods as less affordable and accessible and purchased unhealthy foods more frequently than men. Policies and programs are needed to improve healthy food access, lower costs, and promote gender equity in food acquisition.